Effects of the question-and-answer relationship strategy on students’ reading comprehension and critical thinking - Tsegaye Girma; Marew Alemu; Sefa Meka (Bahir Dar Journal of Education)
This research aimed to determine whether the Question-and-Answer Relationship (QAR) strategy can improve students’ reading comprehension of narrative texts and critical thinking skills in Amharic. The study employed a quasi-experimental pretest-posttest design. A total of 118 seventh graders from Addis Amba Elementary School in Bahir Dar were selected and randomly assigned to either the intervention group (taught reading comprehension using QAR) or the control group (taught according to the grade level curriculum) for 14 sessions. Data were collected through reading comprehension and critical thinking tests. Analysis of variance (one-way ANOVA) revealed significant effects (p < 0.05) and large effect sizes (η² > 0.14) of the QAR strategy on both reading comprehension of narrative texts (F (1,116) = 33.35, p < .001, η² = .223) and critical thinking (F (1,116) = 28.074, p < .001, η² = .195). Findings suggest that the QAR strategy is effective in enhancing students’ reading comprehension of narrative texts and critical thinking skills within the Amharic context.